Effectiveness of Implementing ITE Laws and Investigations of Damnation through Social Media - Satria Ardi Yana; Bambang Tri Bawono (Law Development Journal, 2020)
Social media is also often used as a place to show off the public to post sparkling luxury. The formulation of the problem and the purpose of this study is the effectiveness of the implementation of the ITE Law and investigations of criminal defamation through social media in the conception of legal certainty.Obstacles and Efforts in the process of investigating criminal defamation through social media based on the ITE Law.The research methodology is a sociological juridical legal approach and the specification in this research is descriptive analytical. The theory used is the theory of legal effectiveness and the theory of legal certainty. The results showed that the handling of criminal defamation through social media based on the ITE Law in society has not been effective. The fact is the increasing number of criminal acts of defamation from year to year, and the mode of crime. The first obstacle is the Search for Perpetrators through social media used by defamation facilities, the two factors of inadequate facilities and infrastructure, the third is the difficulty of disclosing evidence, the fourth is the amount of budget required by the police in the process of proving a case using expert witnesses, and the fifth difference in legal perspectives from Social media founding countries.